The Use of Repetition as Self-Repair of an Efl Learner - Haniah, Amanda Ummu; Sasongko, Febry Khunto; Fauziati, Endang (Language Circle: Journal of Language and Literature, 2020)
Self-repair is one of the language learning strategies of second language learners that are distinctly different from each other. This study aims to investigate the use of repetition as self-repair in academic speaking. The researcher tried to find the types of lexical elements which frequently repeated in the academic speaking and dig up the underlying reason behind the repetition as self-repair. A case study was conducted using human instruments and interviews to collect the data. Once the data filled, the researcher analyzed the data by implementing a data archive, trying to expand the codes, evaluating the data sets, and wrapping up the data. The findings from this study revealed that the participants in this study might have used English in speech situations in which they would have used recycling the mistake word. The result of the study found that the participant did indeed self-repair Type D, which consisted of repetition and replacement of one lexical item, and nouns became the most repeated lexical item in the academic speaking. This was a delay strategy as she waited to restart the speech as she needed to think about the next word so that the listeners didn't misinterpret her. Twisted tongue and slip of tongue as a result of the participant’s first language interference contributed to the repetition of certain lexical elements as self-repair.